2007
DOI: 10.3390/medicina44090084
|View full text |Cite
|
Sign up to set email alerts
|

The alcoholic lung disease: Historical background and clinical features

Abstract: Summary. The purpose of this review article is to prove the damage that alcohol causes to the respiratory system. We will make a brief review of alcohols history in the course of the centuries till nowadays. The problem of addiction to alcohol (alcoholism) will be examined for several countries.Alcohol's metabolism is another topic to be discussed parallel to its pharmacological action. In addition, alcohol's impact on the respiratory system varies from damaging the mucociliary system to the regulation of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Indirectly, alcohol and its metabolites may damage the endocrine system and disrupt the actions of hormones like cortisol, testosterone, growth hormone, and prolactin which, in turn, may affect pulmonary function or the function of related organs. For example, both alcohol and its metabolic products have been shown to interfere with glucose and lipid metabolism [ 90 , 92 ].…”
Section: Alcohol and Mechanisms Of Lung Injurymentioning
confidence: 99%
“…Indirectly, alcohol and its metabolites may damage the endocrine system and disrupt the actions of hormones like cortisol, testosterone, growth hormone, and prolactin which, in turn, may affect pulmonary function or the function of related organs. For example, both alcohol and its metabolic products have been shown to interfere with glucose and lipid metabolism [ 90 , 92 ].…”
Section: Alcohol and Mechanisms Of Lung Injurymentioning
confidence: 99%
“…Alcohol abuse alone does not cause acute lung injury though it does increase risk for infection and acute respiratory distress syndrome (Guidot & Hart, 2005). Damage due to concurrent drug and tobacco use is often indistinguishable (Karkoulias et al, 2008) but can be additive (Fligiel et al, 1997). Future research should identify the extent to which clients in drug treatment have respiratory problems, the degree to which respiratory problems are attributable to tobacco or other drug use, and whether quitting smoking helps ameliorate these problems.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol abuse is common in all social classes in the world [ 1 ]. Chronic consumption or acute excessive consumption of alcohol is harmful for important organs including the lung [ 2 ]. Although the absorbed alcohol is mainly metabolized in the liver, the unmetabolized portion enters the circulation and via pulmonary vessels reaches the lung where it affects its homeostasis or causes injury of local tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the absorbed alcohol is mainly metabolized in the liver, the unmetabolized portion enters the circulation and via pulmonary vessels reaches the lung where it affects its homeostasis or causes injury of local tissue [ 3 ]. It has been reported that the inhalation of alcohol compromises lung epithelial barrier function and induces lung edema [ 2 ]. The mechanism is not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation